2021
DOI: 10.3390/nu13124244
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Effects on Bone Mineral Density in Men

Abstract: In contrast to postmenopausal women, evidence for a favorable effect of exercise on Bone Mineral Density (BMD) is still limited for men. This might be due to the paucity of studies, but also to the great variety of participants and study characteristics that may dilute study results. The aim of the present systematic review and meta-analysis was to evaluate the effect of exercise on BMD changes with rational eligibility criteria. A comprehensive search of six electronic databases up to 15 March 2021 was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 43 publications
0
11
0
5
Order By: Relevance
“…In parallel, against our expectation, with its close interaction of exercise parameters, the complexity of exercise might have also confounded our analysis of intensity progression and study duration. Since the methodologically correct approach for addressing this problem, i.e., trials with two exercise arms that differ only in the given component of interest (e.g., exercise frequency; [37]), was not available 4 in the domain of fracture reduction, corresponding exercise recommendations have to be derived from more dedicated metaanalyses in the area of osteoporosis [38][39][40] or fall reduction [2,41] or even better: from randomized controlled trials with similar or comparable training aims and cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, against our expectation, with its close interaction of exercise parameters, the complexity of exercise might have also confounded our analysis of intensity progression and study duration. Since the methodologically correct approach for addressing this problem, i.e., trials with two exercise arms that differ only in the given component of interest (e.g., exercise frequency; [37]), was not available 4 in the domain of fracture reduction, corresponding exercise recommendations have to be derived from more dedicated metaanalyses in the area of osteoporosis [38][39][40] or fall reduction [2,41] or even better: from randomized controlled trials with similar or comparable training aims and cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…A large variety of pharmaceutic agents target osteoporosis, most of which are very cost intensive, have potential negative adverse effects, and focus predominately on the bone. In contrast, physical exercise is a low-cost approach providing positive effects on fall risk [ 2 ] and bone strength [ 3 , 4 ] without causing relevant adverse effects [ 5 ]. Thus, exercise might be an excellent strategy for combatting fractures in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise and physical training have been proven to be effective in promoting and maintaining bone mass and strength [ 4 , 5 ]. In 2021, a systematic review and meta-analysis found that exercise increased bone mass at the lumbar spine and femoral neck in men >18 years old [ 6 ]. Another systematic review of randomized controlled trials showed that progressive resistance training improved femoral neck bone mass in 521 individuals at risk of fracture, with the bone mass being 0.02 g/cm 2 higher in the intervention group than in the control group [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dynamisches Krafttraining gilt als bewährte Trainingsform im Bereich muskuloskelettaler Erkrankungen. Tatsächlich berichtet eine Vielzahl von Trainingsstudien von positiven Effekten eines Krafttrainings auf funktionale und morphometrische Muskelgrößen [1], während die Evidenz für positive Effekte auf die Knochendichte-als wesentlicher Prädiktor der Frakturfestigkeit -bei Männerkollektiven bis vor Kurzem als unzureichend galt [2]. Letzteres mag an einer wenig dezidierten trainingswissenschaftlichen Ausrichtung auf die Knochenfestigkeit gelegen haben [2].…”
Section: Introductionunclassified
“…Tatsächlich berichtet eine Vielzahl von Trainingsstudien von positiven Effekten eines Krafttrainings auf funktionale und morphometrische Muskelgrößen [1], während die Evidenz für positive Effekte auf die Knochendichte-als wesentlicher Prädiktor der Frakturfestigkeit -bei Männerkollektiven bis vor Kurzem als unzureichend galt [2]. Letzteres mag an einer wenig dezidierten trainingswissenschaftlichen Ausrichtung auf die Knochenfestigkeit gelegen haben [2]. Folgt man derzeitigen Trainingsempfehlungen [3], wird eine hohe Reizintensität im Sinne einer hohen mechanischen Belastung ("strain magnitude") sowie einer schnellen Bewegungsausführung ("strain rate") als erfolgversprechend angesehen, während Volumenaspekte wie Satz-bzw.…”
Section: Introductionunclassified